Management of Impaired Physical Mobility through Mobility Support (Range of Motion Therapy) in Non Hemorrahagic Stroke Patients at dr. Gondo Suwarno Regional Hospital - Kharisma Nur Hidayah; Joyo Minardo (Proceeding International Collaborative Conference on Multidisciplinary Science, 2026)
Non Hemorrhagic stroke is a neurological condition caused by obstruction of cerebral blood vessels, resulting in impaired nerve function and decreased physical mobility. Patients commonly experience muscle weakness, limited joint movement, and reduced ability to perform activities of daily living. This case study aimed to describe the nursing care provided to a patient with non-hemorrhagic stroke who experienced impaired physical mobility. A qualitative case study approach was applied. Data were obtained through interviews, observations, physical examinations, and documentation review. Nursing care was implemented over three days following the nursing process, including assessment, nursing diagnosis, intervention, implementation, and evaluation. Assessment findings revealed right-sided hemiparesis, leading to the nursing diagnosis of impaired physical mobility. Nursing interventions included mobilization support, Range of Motion (ROM) exercises, and education with demonstrations of passive ROM techniques for the patient's family. Evaluation showed an improvement in muscle strength from Manual Muscle Testing (MMT) grade 0 to grade 2, although the mobility problem had not been fully resolved. In addition, the family was able to understand and independently perform passive ROM exercises. Regular and continuous ROM exercises involving family participation are recommended to enhance the patient's physical mobility and reduce the risk of complications associated with prolonged immobilization.